Analisis Pengaruh Variasi Usia Pada Delay Fase Nefrogram terhadap Enhancement Citra Anatomi Renalis Dalam CT Scan Urologi - Putra, Ryvando Anggrian Damara; Prananto, Legia; Prawestri, Retno (Perhimpunan Radiografer Indonesia (PARI), 2024)
Background: Technically, this research perform CTScans Urology examination using contrast media undertaken at Tangerang Regional General Hospital (RSUD) using delay in 10 second nephrogram phase after conducting arterial scanning over all age variations. This matter is purposely conducted to know whether there is any different influence of renal image enhancement grade over the age variation in the use of delay of nephrogram phase in CT Scans Urology examination, whereas according to the literature, the use of delay on nephrogram phase is 90-110 seconds after the injection of contrast media. Methods: This research applies quantitative method with analytic approach. This research was undertaken in Tangerang Regional General Hospital starting from February up to April 2024. As for the population of this research, they are all the results of CTScans Urology examination executed in Tangerang Regional Hospital conducted starting from February up to April 2024 with as many as 14 patients. Thereafter, the samples used in this research are secondary data with purposive sampling technique as many as 10 samples from the results of CT Scans Urology examination. Results: The results, at the age of ≤ 40 years has grade point average of enhancement 91.92 HU, meanwhile at the age of ≥ 41 years has a grade point average of enhancement 83.84 HU. Conclusions: Can be concluded that there is a different grade point average between the age of ≤ 40 years and the age of ≥ 41 years, however there is not any significant influence if it is seen from the result of T Test test.